Developing Environmental Education Model Based on Local Wisdom - Jahja, Rusfadia Saktiyanti (Universitas Negeri Semarang, 2016)
This article discusses the development of environmental education model based on local wisdom. The study is motivated by the existing conditions in secondary schools, where environmental education merely focuses on students’ cognitive level and does not touch affective and psychomotor aspects. Students only understand the concept of climate changes, but they do not change their daily behavior in solving it. This study was conducted using mixed approach to analyze the need. It was continued with the development of educational models. This model tried to integrate the environmental education with the existing subjects at school. Therefore, the result can be applied in accordance with the local content. Several experts have reviewed the model and it is further tested in schools to be the pilot project.